Composite yarn and method for making same
Patent Information
- Application Number
- CN202611128405.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本申请的一个目的在于提供一种复合纱线,其旨在于克服纤维耐油污能力不足的技术问题
Smart Images

Figure CN122959883A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of textile fiber technology, and in particular to a composite yarn and its preparation method. Background Technology
[0002] Textile fibers inevitably come into contact with oily dirt during daily use, and the ease of stain removal of fabrics is a continuous focus in the field of functional fibers. Once oily dirt adheres to the fiber surface and migrates into the fiber interior, it is difficult to remove completely during subsequent washing. With increased use and washing frequency, fabrics are prone to problems such as graying, re-soiling, and decreased stain removal performance.
[0003] One improvement in related technologies is to slow down the penetration of oil into the fiber by reducing the affinity of the fiber surface for oily substances. However, this also makes it difficult for the fiber surface to be fully wetted by water during washing, and the attached oily dirt is difficult to be effectively removed by the washing liquid, thus reducing the washability of the fabric. Summary of the Invention
[0004] One object of this application is to provide a composite yarn that overcomes the technical problem of insufficient oil resistance of fibers.
[0005] To achieve the above objectives, this application provides a composite yarn comprising: a core layer; a barrier layer disposed outside the core layer, comprising a first matrix and a water-blocking phase dispersed in the first matrix, the water-blocking phase comprising a hydrophobic polymer, and the water-blocking phase being arranged in multiple layers at intervals in the radial direction of the composite yarn; and a hydrophilic layer disposed outside the barrier layer, comprising a second matrix and modified particles dispersed in the second matrix, the modified particles having hydrophilic segments.
[0006] In this application, the composite yarn is provided with a core layer, a barrier layer, and a hydrophilic layer sequentially from the inside out. The hydrophilic layer contains modified particles with hydrophilic segments, which give the surface of the hydrophilic layer an affinity for water molecules. During washing, water molecules can wet the fiber surface, thus facilitating the removal of oily dirt adhering to the fiber surface. The barrier layer contains a water-blocking phase including a hydrophobic polymer. The hydrophobic polymer has a barrier effect on both water and oily liquids, and the water-blocking phase is arranged in multiple layers radially along the composite yarn. This means that when liquid dirt moves radially within the barrier layer, it must bypass multiple layers of water-blocking phases, lengthening the path of liquid dirt from the hydrophilic layer to the core layer, thereby preventing already penetrated liquid from further migrating into the core layer. The hydrophilic layer is located outside the barrier layer, and the two work together functionally: the hydrophilic layer allows the fiber surface to be fully wetted by water during washing through hydrophilic segments, which is beneficial for the peeling and release of surface oil; the barrier layer prevents liquids that seep into the hydrophilic layer from carrying dirt into the core layer through multiple layers of water-blocking phases arranged radially.
[0007] By combining a hydrophilic layer and a barrier layer, the composite yarn achieves a hydrophilic and washable function in the outer layer and a water-blocking and seepage-proof function in the middle layer. Compared with related technologies that slow down oil penetration by reducing the affinity of the fiber surface for oily substances, the hydrophilic layer of this application does not reduce the affinity of the fiber surface for water, but rather uses hydrophilic segments to increase the hydrophilicity of the fiber surface, allowing the washing liquid to fully wet the fiber surface to remove oil stains. At the same time, the radially spaced multiple layers of water-blocking phase in the barrier layer increase the tortuosity of the path for dirt to migrate inward, reducing the possibility of oil stains reaching the core layer. Therefore, this application can improve the stability of detergency performance after multiple washes while maintaining the washability of the fiber.
[0008] According to one embodiment of this application, each water-blocking phase extends along the axial direction of the composite yarn.
[0009] When each water-blocking phase extends along the axial direction of the composite yarn, the water-blocking phase is elongated along the axial direction. Its projection size in the radial direction of the composite yarn is relatively small, which allows more water-blocking phases to be accommodated on the same cross-section of the composite yarn. This results in a denser multi-layered arrangement in the radial direction, increasing the number of water-blocking phase layers that dirt needs to bypass when migrating from the hydrophilic layer to the core layer, increasing the path tortuosity, and thus improving the barrier layer's ability to block the radial migration of dirt.
[0010] According to one embodiment of this application, the coefficient of thermal expansion of the barrier layer is less than that of the core layer.
[0011] Because the thermal expansion coefficient of the barrier layer is less than that of the core layer, when the composite yarn is heated, the expansion of the barrier layer is less than that of the core layer. Therefore, in terms of their relative morphology, the barrier layer expands in the opposite direction to the core layer in the radial direction, and the two are pressed together to avoid gaps between the barrier layer and the core layer.
[0012] According to one embodiment of this application, the barrier layer comprises, by weight, 55 to 80 parts of copolyester, 12 to 32 parts of polyether ester elastomer, 3 to 15 parts of liquid crystal copolyester, and 0.2 to 1.0 parts of reactive compatibilizer.
[0013] According to one embodiment of this application, the size of the water-blocking phase in the radial direction of the composite yarn is 50 nm to 500 nm.
[0014] According to one embodiment of this application, the water-blocking phase is an oriented dispersed phase formed from a liquid crystal copolyester.
[0015] According to one embodiment of this application, the modified particles comprise nano-inorganic particles with hydrophilic segments attached to the surface of the nano-inorganic particles.
[0016] According to one embodiment of this application, the hydrophilic layer comprises, by weight, 55 to 82 parts of copolyester, 15 to 40 parts of polyether-modified polyester, and 0.5 to 5.0 parts of nano-inorganic particles.
[0017] According to one embodiment of this application, the nano-inorganic particles are nano-silica and / or nano-titanium dioxide.
[0018] According to one embodiment of this application, the average particle size of the nano-inorganic particles is 20 nm to 100 nm.
[0019] According to one embodiment of this application, the surface of the hydrophilic layer has hydrophilic grooves extending along the fiber axis.
[0020] In this application, the surface of the hydrophilic layer has hydrophilic grooves extending along the fiber axis. The hydrophilic grooves increase the contact area between the surface of the hydrophilic layer and the washing liquid, allowing water molecules to soak and spread along the hydrophilic grooves, thereby improving the wetting efficiency of the surface of the hydrophilic layer. At the same time, the capillary channels formed by the hydrophilic grooves help guide the washing liquid to wash away the oily dirt attached to the fiber surface, promoting the removal of oil from the fiber surface.
[0021] According to one embodiment of this application, the depth of the hydrophilic groove is 0.2 μm to 1.5 μm and the width is 0.5 μm to 5 μm.
[0022] According to one embodiment of this application, the core layer includes a third matrix and a reinforcing phase dispersed in the third matrix. The third matrix includes polyester, and the surface of the reinforcing phase is coated with a viscoelastic film, which includes a polyester-compatible material.
[0023] In this application, the core layer includes a third matrix and a reinforcing phase dispersed in the third matrix. The reinforcing phase is used to improve the mechanical properties of the core layer. The surface of the reinforcing phase is coated with a viscoelastic film, which includes a polyester-compatible material. The polyester-compatible material is compatible with the polyester in the third matrix, allowing the viscoelastic film to form a transition interface between the reinforcing phase and the third matrix. Due to the differences in modulus and coefficient of thermal expansion between the reinforcing phase and the third matrix, deformation differences will occur between the reinforcing phase and the third matrix during fiber stretching, bending, or hot water washing. If the reinforcing phase is in direct contact with the third matrix, the deformation difference can easily form interfacial microvoids around the reinforcing phase, becoming channels for dirt to migrate into the fiber interior. The viscoelastic film coating the surface of the reinforcing phase can buffer the deformation difference between the reinforcing phase and the third matrix through its own viscoelastic deformation, reducing the probability of interfacial microvoid formation, thereby reducing defect channels inside the core layer.
[0024] According to one embodiment of this application, the thickness of the viscoelastic film is 20 nm to 150 nm; and / or, the viscoelastic film has a peak value of dynamic mechanical loss factor tanδ in the temperature range of 35°C to 60°C.
[0025] According to one embodiment of this application, the core layer comprises, by weight, 85 to 96 parts of polyester, 2 to 10 parts of polyether ester elastomer, 1.5 to 6.0 parts of reinforcing phase, and 0.05 to 0.8 parts of multifunctional epoxy chain extender.
[0026] According to one embodiment of this application, the reinforcing phase is one or more of silicon carbide whiskers, alumina whiskers, chopped basalt microfibers, or chopped aramid microfibers.
[0027] This application also provides a method for preparing a composite yarn, comprising the following steps: preparing a core layer material; melt-blending a first substrate and a hydrophobic polymer to disperse the hydrophobic polymer in the first substrate to obtain a barrier layer material; melt-blending a second substrate and modified particles to obtain a hydrophilic layer material, wherein the modified particles have hydrophilic segments; sequentially coating the barrier layer material and the hydrophilic layer material onto the core layer material and then performing coaxial spinning and drawing to obtain a composite yarn.
[0028] According to one embodiment of this application, the preparation of the core layer material includes: silanizing the reinforcing phase; melt-blending the silanized reinforcing phase with polyester, polyether ester elastomer and multifunctional epoxy chain extender to form a viscoelastic film in situ on the surface of the reinforcing phase, thereby obtaining the core layer material.
[0029] In this application, the reinforcing phase undergoes a silanization pretreatment to form a surface layer containing reactive organic groups, thereby improving the interfacial bonding between the reinforcing phase and the polyester matrix. When the silanized reinforcing phase is melt-blended with polyester, polyether ester elastomer, and a multifunctional epoxy chain extender, the polyether ester elastomer tends to migrate towards the surface of the reinforcing phase, while the multifunctional epoxy chain extender promotes reactive bonding between the interfacial region and the polyester matrix, thus forming a viscoelastic film in situ on the surface of the reinforcing phase. This in-situ formation method ensures good interfacial bonding between the viscoelastic film and both the reinforcing phase surface and the polyester matrix, which is beneficial for maintaining the structural integrity of the viscoelastic film during subsequent spinning and use.
[0030] According to one embodiment of this application, the first substrate comprises a copolyester and a polyether ester elastomer, and the hydrophobic polymer comprises a liquid crystal copolyester.
[0031] According to one embodiment of this application, the mass ratio of the core layer material, the barrier layer material, and the hydrophilic layer material is 60-78:8-20:12-30.
[0032] According to one embodiment of this application, the apparent viscosities of the core layer material, the barrier layer material, and the hydrophilic layer material during the spinning process are η1, η2, and η3, respectively, with η1:η2:η3 = 1:0.80-1.20:0.60-1.00.
[0033] According to one embodiment of this application, the total draw ratio is 2.8 to 4.0 times.
[0034] Other advantages, objectives and features of this application will be partly apparent from the description below, and partly understood by those skilled in the art through study and practice of this application. Attached Figure Description
[0035] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0036] Figure 1 This is a schematic cross-sectional view of the composite yarn provided in the embodiments of this application;
[0037] Figure 2 This is one of the flowcharts illustrating the method for preparing composite yarn provided in the embodiments of this application; Figure 3 This is the second schematic flowchart of the method for preparing composite yarn provided in the embodiments of this application.
[0038] Explanation of icon numbers: 1. Core layer; 11. Reinforcing phase; 2. Barrier layer; 21. Water-blocking phase; 3. Hydrophilic layer; 31. Modified particles; 32. Hydrophilic groove. Detailed Implementation
[0039] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0040] Textile fibers inevitably come into contact with oily dirt during daily use, and the easy stain removal performance of fabrics is a continuous focus in the field of functional fibers.
[0041] One improvement in related technologies is to slow down the penetration of oil stains into the fiber interior by reducing the affinity of the fiber surface for oily substances. However, while this approach reduces the affinity of the fiber surface for oily substances, it also makes the fiber surface less susceptible to being fully wetted by water during washing, making it difficult for the already attached oily dirt to be effectively removed by the washing liquid, thus reducing the washability of the fabric.
[0042] Furthermore, for polyester yarns containing reinforcing phases, the reinforcing phase and the continuous polyester phase differ in modulus, coefficient of thermal expansion, and deformation recovery ability. During stretching, bending, and hot water washing, tiny interfacial voids or capillary channels will form around the reinforcing phase. Oil, sebum, and oily particulate matter may migrate into the fiber interior along these internal interfaces during use and washing. Even if the fiber surface has a hydrophilic skin or a low surface energy finishing layer, the washing process is difficult to completely remove the dirt that has entered the interior. After repeated washing, the fabric is prone to problems such as graying, re-fouling, and decreased stain removal performance.
[0043] To solve the above-mentioned technical problems, this application provides a composite yarn, referring to... Figure 1 ,include: Core layer 1; Barrier layer 2, sleeved outside core layer 1, includes a first matrix and a water-blocking phase 21 dispersed in the first matrix. The water-blocking phase 21 includes a hydrophobic polymer, and the water-blocking phase 21 is arranged in multiple layers at intervals in the radial direction of the composite yarn. The hydrophilic layer 3 is disposed outside the barrier layer 2 and includes a second matrix and modified particles 31 dispersed in the second matrix. The modified particles 31 have hydrophilic segments.
[0044] In this application, the composite yarn is provided with a core layer 1, a barrier layer 2, and a hydrophilic layer 3 sequentially from the inside out. The hydrophilic layer 3 contains modified particles 31 with hydrophilic segments, which give the surface of the hydrophilic layer 3 an affinity for water molecules. During washing, water molecules can wet the fiber surface, thus facilitating the removal of oily dirt adhering to the fiber surface. The barrier layer 2 contains a water-blocking phase 21 including a hydrophobic polymer. The hydrophobic polymer has a barrier effect on both water and oily liquids, and the water-blocking phase 21 is arranged in multiple layers radially along the composite yarn. This means that when liquid dirt moves radially in the barrier layer 2, it must bypass multiple layers of water-blocking phase 21, extending the path of liquid dirt from the hydrophilic layer 3 to the core layer 1, thereby preventing the already penetrated liquid from further migrating into the core layer 1. The hydrophilic layer 3 is located outside the barrier layer 2, and the two work together functionally: the hydrophilic layer 3 allows the fiber surface to be fully wetted by water during washing through hydrophilic segments, which is beneficial for the peeling and release of surface oil stains; the barrier layer 2 prevents liquids that seep into the hydrophilic layer 3 from carrying dirt into the core layer 1 through multiple layers of water-blocking phases 21 arranged radially.
[0045] Through the cooperation of the hydrophilic layer 3 and the barrier layer 2, the composite yarn achieves a hydrophilic and washable function in the outer layer and a water-blocking and seepage-proof function in the middle layer. Compared with the related technologies that slow down oil penetration by reducing the affinity of the fiber surface for oily substances, the hydrophilic layer 3 of this application does not reduce the affinity of the fiber surface for water, but uses hydrophilic segments to increase the hydrophilicity of the fiber surface, so that the washing liquid can fully wet the fiber surface to remove oil stains; at the same time, the radially spaced multiple layers of water-blocking phase 21 in the barrier layer 2 can increase the tortuosity of the path of dirt migration inward, reducing the possibility of oil stains reaching the core layer 1. Therefore, this application can improve the stability of detergency performance after multiple washes while maintaining the washability of the fiber.
[0046] It should be noted that the hydrophobic polymer in this application refers to a polymer that has low affinity or low permeability to aqueous and oily liquids, such as liquid crystal copolyesters and other polymers with highly oriented structures and dense molecular arrangements. Their molecular chains are tightly arranged, making it difficult for liquid molecules to penetrate, thereby playing a barrier role.
[0047] According to one embodiment of this application, each water-blocking phase 21 extends along the axial direction of the composite yarn.
[0048] When each water-blocking phase 21 extends along the axial direction of the composite yarn, the water-blocking phase 21 is elongated along the axial direction. Its projection size in the radial direction of the composite yarn is relatively small, which allows more water-blocking phases 21 to be accommodated on the same cross section of the composite yarn. This results in a denser multi-layer arrangement in the radial direction, increasing the number of water-blocking phases 21 that dirt needs to bypass when migrating from the hydrophilic layer 3 to the core layer 1, increasing the path tortuosity, and thus improving the barrier layer 2's ability to block the radial migration of dirt.
[0049] For example, the water-blocking phase 21 extends along the axial direction of the composite yarn, which can be achieved through drawing orientation during the spinning process. During drawing, the hydrophobic polymer dispersed in the first matrix is oriented along the fiber axial direction under the action of the stretching flow field, thereby forming an axially extending shape.
[0050] According to one embodiment of this application, the coefficient of thermal expansion of the barrier layer 2 is less than that of the core layer 1.
[0051] Since the coefficient of thermal expansion of the barrier layer 2 is less than that of the core layer 1, when the composite yarn is heated, the expansion of the core layer 1 is greater than that of the barrier layer 2. The core layer 1 expands outward and squeezes the barrier layer 2, so that the barrier layer 2 and the core layer 1 are tightly fitted together, preventing gaps from appearing between the barrier layer 2 and the core layer 1 due to temperature changes, thereby preventing gaps from becoming channels for dirt to migrate from the barrier layer 2 to the core layer 1.
[0052] Furthermore, the thermal expansion coefficient of the barrier layer 2 is less than that of the core layer 1. This means that within the operating temperature range of the composite yarn, such as the washing temperature range of 40°C to 60°C, the radial thermal expansion of the barrier layer 2 is less than that of the core layer 1. This difference in thermal expansion coefficient can be achieved through the selection, proportion, or structure of the materials of the barrier layer 2 and the core layer 1. For example, the barrier layer 2 may contain components with high rigidity, such as liquid crystal copolyester, which has a relatively low thermal expansion coefficient; while the core layer 1 may use polyester as the main matrix, which has a relatively high thermal expansion coefficient.
[0053] According to one embodiment of this application, the barrier layer 2 comprises, by weight, 55 to 80 parts of copolyester, 12 to 32 parts of polyether ester elastomer, 3 to 15 parts of liquid crystal copolyester, and 0.2 to 1.0 parts of reactive compatibilizer. Exemplarily, the content of copolyester can be 55, 60, 65, 70, 75, or 80 parts; the content of polyether ester elastomer can be 12, 18, 22, 26, or 32 parts; the content of liquid crystal copolyester can be 3, 6, 9, 12, or 15 parts; and the content of reactive compatibilizer can be 0.2, 0.4, 0.6, 0.8, or 1.0 parts.
[0054] In this embodiment, the copolyester serves as the continuous phase matrix of the barrier layer 2, providing a fiber-forming continuous phase for the barrier layer 2. The copolyester can be an isophthalic acid-modified polyester, an adipic acid-modified polyester, or a polyester copolymer containing a small amount of flexible segments. A polyether ester elastomer is used to impart reversible radial expansion capability to the barrier layer 2 within the washing temperature range, enabling the barrier layer 2 to undergo limited expansion upon heating and remain adhered to the core layer 1. A liquid crystal copolyester is used to form the water-blocking phase 21, forming a nanoscale dispersed phase under melt shear and tensile orientation. A reactive compatibilizer is used to reduce the interfacial tension between the liquid crystal copolyester and the continuous phase, stabilizing the dispersed phase size. The reactive compatibilizer can be a copolymer containing epoxy groups, anhydride groups, or isocyanate-terminated groups.
[0055] When the polyether ester elastomer content is less than 12 parts, the reversible radial expansion response of the barrier layer 2 is insufficient, resulting in decreased adhesion to the core layer 1 within the washing temperature range. When the polyether ester elastomer content is greater than 32 parts, the modulus of the barrier layer 2 is too low, making it prone to interlayer thickness fluctuations due to stretching stress during the composite spinning process. When the liquid crystal copolyester content is less than 3 parts, the number of orientation barrier paths formed is insufficient, resulting in limited radial barrier capability. When the liquid crystal copolyester content is greater than 15 parts, the probability of contact between dispersed phases increases, leading to decreased melt flow stability.
[0056] According to one embodiment of this application, the dimension of the water-blocking phase 21 in the radial direction of the composite yarn is 50 nm to 500 nm. Exemplarily, the dimension of the water-blocking phase 21 in the radial direction of the composite yarn can be 50 nm, 80 nm, 150 nm, 300 nm, or 500 nm. More preferably, it is 80 nm to 300 nm.
[0057] The size of the water-blocking phase 21 in the radial direction of the composite yarn is controlled within the range of 50nm to 500nm, so that the water-blocking phase 21 has an appropriate thickness in the radial direction to exert its barrier function, while avoiding the water-blocking phase 21 being too large, which would affect the continuity and spinnability of the barrier layer 2. If the radial size of the water-blocking phase 21 is too small, the barrier effect of a single water-blocking phase 21 on liquid is limited and the processing cost increases significantly; if the radial size of the water-blocking phase 21 is too large, the number of water-blocking phases 21 that can be accommodated on the same cross-section decreases, the density of the radial multilayer arrangement decreases, and the barrier layer 2's ability to block liquid contaminants is reduced.
[0058] According to one embodiment of this application, the water-blocking phase 21 is an oriented dispersed phase formed from a liquid crystal copolyester.
[0059] Liquid crystal copolyesters possess a highly oriented molecular chain structure and a dense molecular arrangement, making it difficult for liquid molecules to penetrate and effectively blocking the radial migration of liquids. When liquid crystal copolyesters are subjected to shearing and stretching in the molten state, they easily orient themselves along the fiber axis, forming an axially extending oriented dispersed phase, which in turn forms a multi-layered barrier structure in the radial direction.
[0060] According to one embodiment of this application, the modified particle 31 comprises nano-inorganic particles with hydrophilic segments attached to the surface of the nano-inorganic particles.
[0061] The nano-inorganic particles serve as the carriers of the modified particles 31, with hydrophilic segments attached to their surface. This gives the modified particles 31 both the rigidity of the nano-inorganic particles and the hydrophilicity of the hydrophilic segments. After the nano-inorganic particles are embedded within the hydrophilic layer 3, the hydrophilic segments attached to their surface face the surface of the hydrophilic layer 3, providing a lasting hydrophilic property to the surface of the hydrophilic layer 3. Simultaneously, the rigidity of the nano-inorganic particles makes them less likely to detach from the hydrophilic layer 3 during washing and friction, which helps maintain the stability of the hydrophilic properties after multiple washes.
[0062] According to one embodiment of this application, the hydrophilic layer 3 comprises, by weight, 55 to 82 parts of copolyester, 15 to 40 parts of polyether-modified polyester, and 0.5 to 5.0 parts of nano-inorganic particles. Exemplarily, the content of copolyester can be 55, 62, 70, 76, or 82 parts; the content of polyether-modified polyester can be 15, 22, 28, 34, or 40 parts; and the content of nano-inorganic particles can be 0.5, 1.5, 3.0, 4.0, or 5.0 parts.
[0063] In this embodiment, the copolyester serves as the fiber-forming continuous phase of the hydrophilic layer 3, the polyether-modified polyester provides hydrophilic segments, and the nano-inorganic particles provide the surface micro-roughness structure and the forming induction points for the hydrophilic grooves 32. The polyether segments in the polyether-modified polyester have high polarity and water molecule affinity, and after melt blending, they are distributed within the copolyester continuous phase, giving the surface of the hydrophilic layer 3 hydrophilic properties.
[0064] According to one embodiment of this application, the nano-inorganic particles are nano-silica and / or nano-titanium dioxide.
[0065] Nano-silica contains a large number of hydroxyl groups on its surface, which is beneficial for improving hydrophilic wettability; nano-titanium dioxide is beneficial for improving surface polarity and stain resistance. Nano-silica and nano-titanium dioxide can be used alone or in combination at a certain mass ratio. In a preferred embodiment, the nano-inorganic particles are a mixture of nano-silica and nano-titanium dioxide at a mass ratio of 70:30 to 30:70.
[0066] According to one embodiment of this application, the average particle size of the nano-inorganic particles is 20 nm to 100 nm. Exemplarily, the average particle size of the nano-inorganic particles can be 20 nm, 40 nm, 50 nm, 80 nm, or 100 nm. More preferably, it is 30 nm to 80 nm.
[0067] The average particle size of the nano-inorganic particles is controlled within the range of 20nm to 100nm, so that the nano-inorganic particles can maintain a good dispersion state in the hydrophilic layer 3. This avoids the filtration pressure from being too large during spinning or the surface roughness of the hydrophilic layer 3 being too large, while also avoiding the particle size from being too small, which would cause the particles to easily agglomerate and affect the dispersion uniformity.
[0068] It should be noted that the particle size of the nano-inorganic particles in this application refers to the equivalent spherical diameter of the nano-inorganic particles, that is, the diameter of a sphere with the same volume as the particle. Particle size can be directly observed and measured using a transmission electron microscope. Specifically, the nano-inorganic particles are dispersed in a solvent and dropped onto a copper grid. After drying, images are captured under a transmission electron microscope. At least 200 particles are randomly selected, and the equivalent diameter of each particle is measured using image analysis software. The arithmetic mean is taken as the average particle size. Particle size can also be measured using dynamic light scattering. A laser particle size analyzer is used to test the dilute dispersion of the nano-inorganic particles, and the average particle size is characterized by the volume median diameter (D50).
[0069] According to one embodiment of this application, the surface of the hydrophilic layer 3 has hydrophilic grooves 32 extending along the fiber axis.
[0070] In this application, the surface of the hydrophilic layer 3 has hydrophilic grooves 32 extending along the fiber axis. The hydrophilic grooves 32 increase the contact area between the surface of the hydrophilic layer 3 and the washing liquid, allowing water molecules to wet and spread along the hydrophilic grooves 32, thereby improving the wetting efficiency of the surface of the hydrophilic layer 3. At the same time, the capillary channels formed by the hydrophilic grooves 32 help guide the washing liquid to wash away the oily dirt attached to the fiber surface, promoting the removal of oil from the fiber surface.
[0071] In one embodiment of this application, the hydrophilic groove 32 can be naturally formed during the spinning process through the combined effects of stretching and cooling shrinkage. The hydrophilic layer 3 contains non-homogeneous phases such as nano-inorganic particles. The nano-inorganic particles form microscale morphology induction points on the surface of the hydrophilic layer 3. During the stretching and cooling process, due to the presence of polyether-modified polyester and nano-inorganic particles, the shrinkage rates of the components in the hydrophilic layer 3 are different, and under the induction of the nano-inorganic particles, hydrophilic grooves 32 extending along the fiber axis are formed.
[0072] According to one embodiment of this application, the depth of the hydrophilic groove 32 is 0.2 μm to 1.5 μm, and the width is 0.5 μm to 5 μm. For example, the depth of the hydrophilic groove 32 can be 0.2 μm, 0.5 μm, 0.8 μm, 1.2 μm, or 1.5 μm; the width of the hydrophilic groove 32 can be 0.5 μm, 1 μm, 2 μm, 3.5 μm, or 5 μm.
[0073] The depth of the hydrophilic tank 32 is controlled within the range of 0.2μm to 1.5μm, and the width is controlled within the range of 0.5μm to 5μm, so that the hydrophilic tank 32 has an appropriate capillary channel size to achieve the wetting and spreading effect of the washing liquid, while avoiding the hydrophilic tank 32 being too deep or too wide, which would weaken the structural strength of the hydrophilic layer 3.
[0074] According to one embodiment of this application, the core layer 1 includes a third matrix and a reinforcing phase 11 dispersed in the third matrix. The third matrix includes polyester, and the surface of the reinforcing phase 11 is coated with a viscoelastic film, which includes a polyester-compatible material.
[0075] In this application, the core layer 1 includes a third matrix and a reinforcing phase 11 dispersed in the third matrix. The reinforcing phase 11 is used to improve the mechanical properties of the core layer 1. The surface of the reinforcing phase 11 is coated with a viscoelastic film, which includes a polyester compatible material. The polyester compatible material is compatible with the polyester in the third matrix, allowing the viscoelastic film to form a transition interface between the reinforcing phase 11 and the third matrix. Due to the differences in modulus and coefficient of thermal expansion between the reinforcing phase 11 and the third matrix, deformation differences will occur between the reinforcing phase 11 and the third matrix during fiber stretching, bending, or hot water washing. If the reinforcing phase 11 is in direct contact with the third matrix, the deformation difference can easily form interfacial microvoids around the reinforcing phase 11, becoming channels for dirt to migrate into the fiber interior. The viscoelastic film coating the surface of the reinforcing phase 11 can buffer the deformation difference between the reinforcing phase 11 and the third matrix through its own viscoelastic deformation, reducing the probability of interfacial microvoid formation, thereby reducing defect channels inside the core layer 1.
[0076] The polyester compatible material in this application refers to a material that can form a good interfacial bond with the polyester matrix, such as a coating material formed by the in-situ reaction of polyether ester elastomer and multifunctional epoxy chain extender on the surface of reinforcing phase 11. The polyether ester segments in this material are compatible with the polyester matrix and also have viscoelastic characteristics.
[0077] According to one embodiment of this application, the thickness of the viscoelastic film is from 20 nm to 150 nm. For example, the thickness of the viscoelastic film can be 20 nm, 50 nm, 80 nm, 120 nm or 150 nm.
[0078] The thickness of the viscoelastic film is controlled within the range of 20nm to 150nm. When the thickness of the viscoelastic film is less than 20nm, the rigidity difference between the reinforcing phase 11 and the third matrix is difficult to be adequately buffered, and the deformation buffering capacity of the viscoelastic film is insufficient. When the thickness of the viscoelastic film is greater than 150nm, the actual rigidity contribution of the reinforcing phase 11 to the core layer 1 is excessively weakened, and the melt viscosity of the core layer 1 may increase, affecting the spinning processability.
[0079] According to one embodiment of this application, the viscoelastic film has a peak value of dynamic mechanical loss factor tanδ in the temperature range of 35°C to 60°C.
[0080] The viscoelastic film exhibits a peak value of dynamic mechanical loss factor (tanδ) in the temperature range of 35℃ to 60℃, indicating that the viscoelastic film possesses viscoelastic energy dissipation capability within this temperature range. The 35℃ to 60℃ temperature range covers the typical temperature range for hot water washing. The presence of a peak value of tanδ within this temperature range allows the viscoelastic film to effectively buffer the interfacial stress generated by the difference in thermal expansion between the reinforcing phase 11 and the third matrix during washing, thereby reducing the probability of interfacial micropore formation.
[0081] It should be noted that the dynamic mechanical loss factor tanδ in this application refers to the ratio of the loss modulus to the storage modulus in dynamic mechanical analysis and testing, i.e., tanδ = E″ / E′, where E″ is the loss modulus and E′ is the storage modulus. The tanδ value reflects the material's ability to convert mechanical energy into thermal energy. Under the same test frequency, strain amplitude, and temperature rise conditions, the larger the tanδ value, the stronger the viscoelastic energy dissipation capacity of the material. The tanδ peak value refers to the maximum value appearing in the curve of tanδ changing with temperature. The temperature corresponding to the tanδ peak value is usually related to the glass transition temperature or secondary relaxation transition of the material. In this application, the viscoelastic film has a tanδ peak value in the temperature range of 35℃ to 60℃, indicating that the viscoelastic film undergoes molecular chain segment relaxation motion in this temperature range, has a strong viscoelastic energy dissipation capacity, and can dissipate the interfacial stress generated by the deformation difference between the reinforcing phase 11 and the third matrix through internal friction.
[0082] The tanδ peak value can be obtained by testing with a dynamic thermomechanical analyzer. The specific method is as follows: place the core layer material 1 containing the viscoelastic film or the composite yarn sample in the dynamic thermomechanical analyzer, and perform temperature scanning in the temperature range of -50℃ to 150℃ with a frequency of 1Hz to 10Hz and a heating rate of 2℃ / min to 5℃ / min in the stretching or bending mode. Record the curves of the change of storage modulus E′, loss modulus E″ and tanδ with temperature, and read the peak value and its corresponding temperature on the tanδ-temperature curve.
[0083] According to one embodiment of this application, the core layer 1 comprises, by weight, 85 to 96 parts of polyester, 2 to 10 parts of polyether ester elastomer, 111.5 to 6.0 parts of reinforcing phase 11, and 0.05 to 0.8 parts of multifunctional epoxy chain extender. Exemplarily, the content of polyester may be 85, 88, 91, 93, or 96 parts; the content of polyether ester elastomer may be 2, 4, 6, 8, or 10 parts; the content of reinforcing phase 11 may be 1.5, 3.0, 4.0, 5.0, or 6.0 parts; and the content of multifunctional epoxy chain extender may be 0.05, 0.15, 0.3, 0.5, or 0.8 parts.
[0084] In this embodiment, polyester serves as the continuous phase matrix of core layer 1, providing core layer 1 with the main mechanical properties and fiber-forming ability; polyether ester elastomer is used to provide viscoelastic segments in the viscoelastic film; multifunctional epoxy chain extender is used to participate in the interfacial reaction during melt blending, promoting the in-situ formation of the viscoelastic film on the surface of reinforcing phase 11. The polyester matrix can be fiber-grade polyethylene terephthalate.
[0085] According to one embodiment of this application, the reinforcing phase 11 is one or more of silicon carbide whiskers, alumina whiskers, chopped basalt microfibers, or chopped aramid microfibers.
[0086] Silicon carbide whiskers and alumina whiskers belong to inorganic reinforcing phase 11, possessing high modulus and high hardness, which can effectively improve the rigidity and dimensional stability of core layer 1; chopped basalt microfibers have good heat resistance and chemical stability; chopped aramid microfibers have good toughness and fatigue resistance. Reinforcing phase 11 can be used alone or in combination with two or more of the above materials.
[0087] In a preferred embodiment, the reinforcing phase 11 is a silicon carbide whisker with an average diameter of 0.2 μm to 1.0 μm, an average length of 5 μm to 25 μm, and an aspect ratio of 10 to 50. More preferably, the silicon carbide whisker has an average diameter of 0.4 μm to 0.8 μm, an average length of 8 μm to 18 μm, and an aspect ratio of 15 to 40.
[0088] To solve the above technical problems, please refer to Figure 2 This application also provides a method for preparing composite yarn, comprising the following steps: S201, Prepare core layer 1 material; S203. The first substrate and the hydrophobic polymer are melt-blended to disperse the hydrophobic polymer in the first substrate, thereby obtaining the barrier layer 2. S205. The second substrate and the modified particles 31 are melt-blended to obtain the hydrophilic layer 3, wherein the modified particles 31 have hydrophilic segments. S207. After sequentially covering the core layer 1 with the barrier layer 2 material and the hydrophilic layer 3 material, coaxial spinning is performed and the yarn is drawn to obtain the composite yarn.
[0089] In this embodiment, core layer 1, barrier layer 2, and hydrophilic layer 3 are prepared separately, and then the three layers are coaxially spun to form a composite yarn comprising core layer 1, barrier layer 2, and hydrophilic layer 3 from the inside out. Through coaxial spinning, each functional component functions within its corresponding layer, achieving a layered configuration of reinforcement, barrier, and hydrophilic functions on the same composite yarn. The technical effects of the composite yarn prepared by this method can be referenced in any of the foregoing embodiments.
[0090] Before implementing the preparation method, each resin raw material can be dried. Polyester, copolyester, polyether-modified polyester, and polyether ester elastomer can be vacuum dried at 120°C to 150°C for 4 to 8 hours to reduce the moisture content to below 60 ppm. Liquid crystal copolyester can be dried at 130°C to 160°C for 3 to 6 hours to reduce hydrolytic degradation during twin-screw extrusion. Nano-silica, nano-titanium dioxide, silicon carbide whiskers, alumina whiskers, chopped basalt microfibers, and chopped aramid microfibers can be dried at 100°C to 130°C for 2 to 5 hours to remove adsorbed water and surface volatiles. Drying treatment can reduce the risk of hydrolysis during melt processing, stabilize the viscosity of each melt layer, and reduce bubbles, breakage, and gel points during spinning.
[0091] Please refer to Figure 3 According to one embodiment of this application, the preparation of core layer 1 material includes: S301. Perform silanization pretreatment on the reinforcing phase 11; S303. The reinforcing phase 11, which has undergone silanization pretreatment, is melt-blended with polyester, polyether ester elastomer and multifunctional epoxy chain extender to form a viscoelastic film in situ on the surface of the reinforcing phase 11, thereby obtaining the core layer 1 material.
[0092] In this application, the reinforcing phase 11 is first pretreated with silanization to form a surface layer containing reactive organic groups, thereby improving the interfacial bonding between the reinforcing phase 11 and the polyester matrix. When the silanized reinforcing phase 11 is melt-blended with polyester, polyether ester elastomer, and a multifunctional epoxy chain extender, the polyether ester elastomer tends to migrate to the surface of the reinforcing phase 11, and the multifunctional epoxy chain extender promotes reactive bonding between the interfacial region and the polyester matrix, thus forming a viscoelastic film in situ on the surface of the reinforcing phase 11. This in-situ formation method ensures good interfacial bonding between the viscoelastic film and both the surface of the reinforcing phase 11 and the polyester matrix, which is beneficial for maintaining the structural integrity of the viscoelastic film during subsequent spinning and use.
[0093] The silanization pretreatment can be carried out as follows: The reinforcing phase 11 is added to a 0.5% to 3.0% (w / w) aqueous alcohol solution of a silane coupling agent, with the water to ethanol mass ratio controlled at 10:90 to 30:70. The pH of the solution is adjusted to 4.0 to 5.5 using acetic acid, and the mixture is stirred at 25°C to 50°C for 30 to 120 minutes. After treatment, the reinforcing phase 11 is filtered, washed, and dried. The drying temperature is controlled at 100°C to 130°C, and the drying time is controlled at 2 to 5 hours. The silane coupling agent can be γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, or methacryloxypropyltrimethoxysilane. After treatment, a surface layer containing silicon-oxygen bonds and reactive organic groups is formed on the surface of the reinforcing phase 11. The product is a dry, free-flowing powder or short fiber aggregate.
[0094] After hydrolysis, the silane coupling agent forms silanol groups, which can condense or adsorb onto the hydroxyl groups on the surface of the inorganic reinforcing phase 11. The organic groups at the other end of the coupling agent face the polyester melt. Under melt blending temperature and shear conditions, the polyether ester elastomer tends to be distributed in the compatibility interface region near the reinforcing phase 11. The multifunctional epoxy chain extender promotes limited reactive bonding between this interface region and the polyester matrix, forming a viscoelastic film.
[0095] Specifically, the surface energy of the reinforcing phase 11, after silanization pretreatment, is reduced, and its interfacial tension with the polyether ester elastomer is lower than its interfacial tension with the matrix polyester. This drives the polyether ester elastomer molecular chains to spontaneously migrate and accumulate on the surface of the reinforcing phase 11 during the initial stage of melt mixing. In the feeding and melting sections, forward conveying elements are used to establish pressure, breaking up initial agglomerates or unevenly coated aggregates through strong shearing, exposing the surface of the reinforcing phase 11, and promoting the polyether ester elastomer to spread uniformly again, achieving interfacial reorganization and densification of the coating layer. At this stage, the multifunctional epoxy chain extender is mainly injected into the molten polyether ester elastomer and reinforcing phase 11 mixture through side feeding. The epoxy groups undergo coupling reactions with the end groups of the polyether ester elastomer and the matrix polyester at the interface, increasing the melt viscosity and elasticity of the interfacial region and preventing desorption or coarsening due to molecular thermal motion during subsequent high-temperature mixing, thus preventing the formation of a viscoelastic film.
[0096] Melt blending can be carried out in a co-rotating twin-screw extruder. The temperatures of zones one through six of the twin-screw extruder can be controlled sequentially as follows: 245°C to 255°C, 255°C to 265°C, 260°C to 275°C, 265°C to 280°C, 265°C to 280°C, and 260°C to 275°C. The die head temperature is controlled at 260°C to 275°C, the screw speed is controlled at 120 rpm to 350 rpm, and the vacuum exhaust pressure is controlled at -0.090 MPa to -0.098 MPa.
[0097] After water cooling, pelletizing, and drying, the core layer 1 material can be used as the core layer 1 feedstock for subsequent coaxial spinning. The intrinsic viscosity of the core layer 1 material chips is controlled to be between 0.62 dL / g and 0.76 dL / g, and the melting point or softening range is matched with the subsequent spinning temperature.
[0098] In a preferred embodiment, the reinforcing phase 11 is a silicon carbide whisker with an average diameter of 0.4 μm to 0.8 μm, an average length of 8 μm to 18 μm, and an aspect ratio of 15 to 40; the silane coupling agent is γ-glycidoxypropyltrimethoxysilane, and the amount of coupling agent is 1.0% to 2.0% of the mass of the silicon carbide whisker; the amount of polyether ester elastomer added is 4% to 8% of the total mass of the core layer 1 material, and the amount of multifunctional epoxy chain extender added is 0.15% to 0.45%.
[0099] According to one embodiment of this application, the first substrate comprises a copolyester and a polyether ester elastomer, and the hydrophobic polymer comprises a liquid crystal copolyester.
[0100] In this embodiment, the first substrate comprises a copolyester and a polyether ester elastomer. The copolyester and the polyether ester elastomer together constitute the continuous phase of the barrier layer 2. The polyether ester elastomer imparts reversible radial expansion capability to the barrier layer 2 within the washing temperature range. The hydrophobic polymer comprises a liquid crystal copolyester. The liquid crystal copolyester forms a nanoscale dispersed phase under melt shearing, and after subsequent stretching and orientation, forms a water-blocking phase 21 oriented along the fiber axis.
[0101] When preparing barrier layer 2, copolyester, polyether ester elastomer, liquid crystal copolyester and reactive compatibilizer are melt-mixed by twin-screw extrusion. The shear strength and residence time are controlled so that the liquid crystal copolyester forms a dispersed phase with a lateral size of 50 nm to 500 nm in the continuous phase of copolyester / polyether ester elastomer.
[0102] The twin-screw extruder can be a co-rotating type with an aspect ratio of 40 to 56. The temperatures in zones one through eight can be controlled sequentially as follows: 235℃ to 245℃, 245℃ to 255℃, 255℃ to 265℃, 260℃ to 275℃, 265℃ to 280℃, 265℃ to 280℃, 260℃ to 275℃, and 255℃ to 270℃. The die head temperature is controlled at 255℃ to 270℃. The screw speed can be controlled from 250 rpm to 600 rpm. The melt residence time can be controlled from 45 s to 180 s. The vacuum exhaust pressure is controlled from -0.085 MPa to -0.098 MPa. To stabilize the dispersed phase size, the liquid crystal copolyester should be premixed with a portion of the copolyester and added from the main feed. The reactive compatibilizer is added via side feeding or liquid metering to the section where the melt is essentially plasticized.
[0103] It should be noted that shear strength is one of the key control parameters for preparing barrier layer 2. When the shear strength is too low, the liquid crystal copolyester cannot be fully broken down and stretched, forming a coarse dispersed phase with a lateral dimension greater than 500 nm. When the shear strength is too high, the liquid crystal copolyester dispersed phase may be over-broken, the interfacial area increases sharply, leading to re-agglomeration in areas with insufficient compatibilizer, while the continuous phase molecular chains are subjected to excessive shear degradation. By jointly controlling the angle of the kneading block, the number of reverse elements, the screw speed, and the feed rate in the screw assembly, the lateral dimension of the dispersed phase can be stabilized between 50 nm and 500 nm, more preferably between 80 nm and 300 nm.
[0104] When preparing the hydrophilic layer 3, copolyester, polyether-modified polyester, and nano-inorganic particles are melt-blended. The nano-inorganic particles should first be mixed with a small amount of polyether-modified polyester or copolyester to prepare a pre-dispersed masterbatch. The content of nano-inorganic particles in the pre-dispersed masterbatch should be 10% to 25%. High-speed mixing, internal mixing, or twin-screw extrusion can be used to prepare the pre-dispersed masterbatch to reduce the degree of secondary agglomeration of the nano-inorganic particles. Melt blending is carried out in a twin-screw extruder, with the temperature controlled at 230℃ to 270℃, the screw speed controlled at 150 rpm to 450 rpm, and the vacuum exhaust pressure controlled at -0.080 MPa to -0.098 MPa.
[0105] In a preferred embodiment, the barrier layer 2 material comprises, by weight, 65 to 72 parts of copolyester, 18 to 26 parts of polyether ester elastomer, 6 to 10 parts of liquid crystal copolyester, and 0.4 to 0.8 parts of reactive compatibilizer.
[0106] According to one embodiment of this application, the mass ratio of core layer 1, barrier layer 2, and hydrophilic layer 3 is 60-78:8-20:12-30. Exemplarily, the mass ratio of core layer 1, barrier layer 2, and hydrophilic layer 3 can be 60:18:22, 65:15:20, 68:14:18, 72:10:18, or 78:8:14.
[0107] The core layer 1 material proportion is controlled at 60% to 78% to ensure that the composite yarn has sufficient load-bearing cross-section and mechanical properties. The barrier layer 2 material proportion is controlled at 8% to 20% to form a continuous ring-shaped barrier layer 2 structure, while avoiding excessive thickness of the barrier layer 2 which would lead to excessive overall fiber rigidity. The hydrophilic layer 3 material proportion is controlled at 12% to 30% to provide a stable outer surface and sufficient hydrophilic functional components.
[0108] According to one embodiment of this application, the apparent viscosities of the core layer 1 material, the barrier layer 2 material, and the hydrophilic layer 3 material during the spinning process are η1, η2, and η3, respectively, with η1:η2:η3=1:0.80-1.20:0.60-1.00.
[0109] Controlling the apparent viscosity ratio of the three melt layers within the aforementioned range is beneficial for maintaining the flow stability of each melt layer and the integrity of the interlayer interfaces during coaxial spinning. The apparent viscosity η2 of the barrier layer 2 material is close to the apparent viscosity η1 of the core layer 1 material, which helps maintain the continuous annular structure of the barrier layer 2. The apparent viscosity η3 of the hydrophilic layer 3 material is slightly lower than the apparent viscosity η1 of the core layer 1 material, which helps the hydrophilic layer 3 to uniformly coat the outside of the barrier layer 2 in the composite spinneret assembly. When η3 is significantly lower than the lower limit of η1, the hydrophilic layer 3 melt is easily thinned in the composite spinneret assembly, risking local exposure of the barrier layer 2; when η3 is higher than η1, it can easily lead to uncontrolled surface roughness of the hydrophilic layer 3 or spinneret breakage.
[0110] According to one embodiment of this application, the total draw ratio is 2.8 to 4.0 times. Exemplarily, the total draw ratio can be 2.8 times, 3.0 times, 3.4 times, 3.8 times, or 4.0 times.
[0111] The total draw ratio is controlled within the range of 2.8 to 4.0. During the drawing process, the continuous polyester phase in the core layer 1 is oriented along the fiber axis, the hydrophobic polymer dispersed phase in the barrier layer 2 is oriented along the fiber axis under the stretching flow field and forms a multi-layered water-blocking phase 21 on the radial section, and the hydrophilic layer 3 forms a hydrophilic groove 32 extending along the fiber axis under the combined action of stretching and cooling shrinkage.
[0112] The drawing process can employ single-stage or multi-stage hot drawing. The preheating roller temperature is 70℃ to 95℃, the main drawing roller temperature is 95℃ to 125℃, and the hot plate or hot box temperature is 120℃ to 155℃. The heat setting temperature is controlled at 135℃ to 165℃ for 5s to 60s, and the heat setting tension can be controlled at 0.05cN / dtex to 0.30cN / dtex. Heat setting is used to fix the molecular orientation and layered cross-sectional morphology formed after drawing, reducing dimensional changes during subsequent winding, weaving, and hot water washing.
[0113] During coaxial spinning, the three layers are melted and plasticized separately using individual screw extruders. The melt temperature of core layer 1 is controlled at 270℃ to 290℃, the melt temperature of barrier layer 2 is controlled at 260℃ to 285℃, and the melt temperature of hydrophilic layer 3 is controlled at 255℃ to 280℃. The temperature of the composite spinning box is controlled at 270℃ to 285℃, and the spinneret temperature is controlled at 268℃ to 282℃. Each layer melt is filtered before entering the composite assembly, with a filtration precision of 10μm to 25μm.
[0114] The composite spinneret assembly employs a three-component coaxial composite spinneret structure. Core layer 1 material enters through a central flow channel, barrier layer 2 material enters through a middle annular flow channel, and hydrophilic layer 3 material enters through an outer annular flow channel. To ensure the barrier layer 2 maintains a continuous annular structure, the annular gap width of the middle annular flow channel is controlled to be 0.05 mm to 0.25 mm, and the annular gap width of the outer annular flow channel is controlled to be 0.08 mm to 0.35 mm. The spinneret orifice diameter is 0.20 mm to 0.45 mm, and the aspect ratio is 2.0 to 4.0.
[0115] Cooling is achieved through side-blowing, with a side-blowing temperature of 18℃ to 28℃, relative humidity of 55% to 75%, and wind speed of 0.25m / s to 0.60m / s. The cooling zone length is 0.8m to 1.5m. Oiling is performed using a hydrophilic spinning oil for polyester filaments, with the oiling rate controlled at 0.4% to 1.0%.
[0116] In a preferred embodiment, the composite yarn has a monofilament fineness of 1.0 dtex to 5.0 dtex, a total multifilament fineness of 50 dtex to 300 dtex, and a winding speed of 2500 m / min to 4500 m / min.
[0117] The beneficial effects of the second aspect described above can be referred to in the first aspect or any possible implementation of the first aspect, and will not be elaborated here. Based on the implementations provided in the above aspects, this application can also be further combined to provide more implementations.
[0118] The technical solution of this application will be further described below through specific embodiments and comparative examples.
[0119] Example 1: Step S1: Select silicon carbide whiskers with an average diameter of 0.5 μm and an average length of 12 μm as the reinforcing phase. Add the silicon carbide whiskers to a 1.5% (w / w) aqueous solution of γ-glycidoxypropyltrimethoxysilane ethanol, adjust the pH to 4.8, stir at 45 °C for 60 min, filter, and dry at 120 °C for 3 h to obtain silanized silicon carbide whiskers.
[0120] Take 91.2 parts by weight of polyester, 5.0 parts by weight of polyether ester elastomer, 0.3 parts by weight of multifunctional epoxy chain extender, and 3.5 parts by weight of silanized silicon carbide whiskers, add them to a twin-screw extruder for melt blending, extrusion temperature 255℃ to 275℃, screw speed 260 rpm, and vacuum exhaust pressure -0.095 MPa to obtain the core layer material.
[0121] Step S2: Take 68 parts by weight of copolyester, 22 parts by weight of polyether ester elastomer, 9 parts by weight of liquid crystal copolyester, and 0.6 parts by weight of reactive compatibilizer, and prepare the barrier layer material by twin-screw extrusion. The extrusion temperature is 245℃ to 275℃, the screw speed is 420rpm, and the residence time is 95s.
[0122] Step S3: Take 70 parts by weight of copolyester, 27 parts by weight of polyether modified polyester, and 3 parts by weight of mixed particles of nano silica and nano titanium dioxide, wherein the mass ratio of nano silica to nano titanium dioxide is 60:40 and the average particle size is 50nm. Add them as pre-dispersed masterbatch and melt blend them at 240℃ to 265℃ to obtain the hydrophilic layer material.
[0123] Step S4: The core layer material, barrier layer material, and hydrophilic layer material are melted and plasticized separately, and fed into the three-component coaxial composite spinneret in a mass ratio of 68:14:18; at the spinning shear rate, the ratio of the apparent viscosity η1 of the core layer material, the apparent viscosity η2 of the barrier layer material, and the apparent viscosity η3 of the hydrophilic layer material is η1:η2:η3=1:1.05:0.82; the spinning box temperature is 278℃, the side blowing temperature is 22℃, the side blowing speed is 0.38m / s, the oiling rate is 0.65%; the total draw ratio is 3.4 times, and the heat setting temperature is 150℃; a composite yarn is obtained.
[0124] Example 2: The difference from Example 1 is that in step S1, alumina whiskers with an average diameter of 0.7 μm and an average length of 16 μm are used as the reinforcing phase; the core layer material formulation is 89.65 parts by weight of polyester, 6.0 parts by weight of polyether ester elastomer, 0.35 parts by weight of multifunctional epoxy chain extender, and 4.0 parts by weight of silanized alumina whiskers.
[0125] In step S1, the screw speed is 300 rpm. In step S2, 64 parts by weight of copolyester, 25 parts by weight of polyether ester elastomer, 10 parts by weight of liquid crystal copolyester, and 0.7 parts by weight of reactive compatibilizer are used, with a screw speed of 460 rpm. In step S3, 30 parts by weight of polyether-modified polyester, 2.5 parts by weight of a mixture of nano-silica and nano-titanium dioxide particles, and 67.5 parts by weight of copolyester are used. In step S4, the three-layer mass ratio is 66:15:19, the total draw ratio is 3.6 times, and the heat setting temperature is 148℃.
[0126] Example 3: The difference from Example 1 is that in step S1, short-cut basalt microfibers with an average diameter of 0.9 μm and an average length of 20 μm are used as the reinforcing phase. The silanization treatment uses an aqueous solution of γ-aminopropyltriethoxysilane with a mass fraction of 1.2%, the treatment temperature is 40°C, and the treatment time is 90 min. The core material formulation is 92.0 parts by weight of polyester, 5.0 parts by weight of polyether ester elastomer, 0.5 parts by weight of multifunctional epoxy chain extender, and 2.5 parts by weight of silanized short-cut basalt microfibers.
[0127] In step S1, the screw speed is 220 rpm; in step S2, there are 72 parts by weight of copolyester, 18 parts by weight of polyether ester elastomer, 8 parts by weight of liquid crystal copolyester, and 0.5 parts by weight of reactive compatibilizer; in step S3, there are 74 parts by weight of copolyester, 24 parts by weight of polyether modified polyester, and 2 parts by weight of nano silica; in step S4, the three-layer mass ratio is 72:10:18, the total draw ratio is 3.2 times, and the heat setting temperature is 155℃.
[0128] Example 4: The difference from Example 1 is that in step S1, short-cut aramid microfibers with an average length of 14 μm are used as the reinforcing phase, with an addition amount of 3.0 parts by weight. The short-cut aramid microfibers are first subjected to plasma activation treatment, and then silanized using methacryloyloxypropyltrimethoxysilane. The amount of silane coupling agent used is 1.5% of the mass of the short-cut aramid microfibers.
[0129] The core layer material formulation consists of 89.75 parts by weight of polyester, 7.0 parts by weight of polyether ester elastomer, 0.25 parts by weight of multifunctional epoxy chain extender, and 3.0 parts by weight of the above-treated short-cut aramid microfibers; in step S2, the formulation consists of 69.6 parts by weight of copolyester, 24 parts by weight of polyether ester elastomer, 6 parts by weight of liquid crystal copolyester, and 0.4 parts by weight of reactive compatibilizer; in step S3, the formulation consists of 70.2 parts by weight of copolyester, 28 parts by weight of polyether-modified polyester, and 1.8 parts by weight of nano-titanium dioxide with an average particle size of 40 nm; in step S4, the three-layer mass ratio is 65:16:19, the total draw ratio is 3.0 times, and the heat setting temperature is 145℃.
[0130] Example 5: The difference from Example 1 is that in step S1, silicon carbide whiskers and chopped aramid microfibers are used as a reinforcing phase, with a mass ratio of silicon carbide whiskers to chopped aramid microfibers of 70:30 and a total addition of 5.0 parts by weight; the core layer material formulation is 88.4 parts by weight of polyester, 6.0 parts by weight of polyether ester elastomer, 0.6 parts by weight of multifunctional epoxy chain extender, and 5.0 parts by weight of the above-mentioned composite reinforcing phase; in step S2, copolyester 60 parts by weight, polyether ester elastomer 28 parts by weight, liquid crystal copolyester 11 parts by weight, reactive compatibilizer 0.9 parts by weight, and screw speed 500 rpm; in step S3, copolyester 62 parts by weight, polyether modified polyester 34 parts by weight, and mixed particles of nano-silica and nano-titanium dioxide 4 parts by weight; in step S4, the three-layer mass ratio is 60:18:22, the total draw ratio is 3.8 times, and the heat setting temperature is 152°C.
[0131] Example 6: The difference from Example 1 is that in step S1, the amount of silicon carbide whiskers added is 3.0 parts by weight, and the core layer material formula is 92.2 parts by weight of polyester, 4.5 parts by weight of polyether ester elastomer, 0.3 parts by weight of multifunctional epoxy chain extender, and 3.0 parts by weight of silanized silicon carbide whiskers; in step S2, there are 75 parts by weight of copolyester, 17 parts by weight of polyether ester elastomer, 7 parts by weight of liquid crystal copolyester, and 0.5 parts by weight of reactive compatibilizer; in step S3, there are 76 parts by weight of copolyester, 22 parts by weight of polyether modified polyester, and 2 parts by weight of nano-silica; in step S4, the three-layer mass ratio is 78:8:14, the spinning box temperature is 280°C, the total draw ratio is 4.0 times, and the heat setting temperature is 165°C.
[0132] Example 7: The difference from Example 1 is that in step S1, the amount of silicon carbide whiskers added is 1.5 parts by weight, and the core layer material formula is 93.0 parts by weight of polyester, 5.0 parts by weight of polyether ester elastomer, 0.5 parts by weight of multifunctional epoxy chain extender, and 1.5 parts by weight of silanized silicon carbide whiskers; in step S2, the copolyester is 68 parts by weight of polyester, 12 parts by weight of polyether ester elastomer, 15 parts by weight of liquid crystal copolyester, and 1.0 part by weight of reactive compatibilizer, and the screw speed is 500 rpm; in step S3, the copolyester is 78.5 parts by weight of polyester, 20 parts by weight of polyether modified polyester, and 1.5 parts by weight of nano-silica; in step S4, the three-layer mass ratio is 65:20:15, the total draw ratio is 2.8 times, and the heat setting temperature is 135°C.
[0133] Example 8: The difference from Example 1 is that in step S1, the amount of silicon carbide whiskers added is 6.0 parts by weight, and the core layer material formulation is 88.5 parts by weight of polyester, 5.0 parts by weight of polyether ester elastomer, 0.5 parts by weight of multifunctional epoxy chain extender, and 6.0 parts by weight of silanized silicon carbide whiskers; in step S2, there are 62 parts by weight of copolyester, 24 parts by weight of polyether ester elastomer, 12 parts by weight of liquid crystal copolyester, and 0.8 parts by weight of reactive compatibilizer; in step S3, there are 65 parts by weight of copolyester, 30 parts by weight of polyether modified polyester, and 5 parts by weight of mixed particles of nano-silica and nano-titanium dioxide; in step S4, the three-layer mass ratio is 62:8:30, the total draw ratio is 3.5 times, and the heat setting temperature is 150°C.
[0134] Comparative Example 1: The difference from Example 1 is that in step S1, the silicon carbide whiskers are not subjected to silanization pretreatment, but are directly melt-blended with polyester, polyether ester elastomer and multifunctional epoxy chain extender.
[0135] Comparative Example 2: The difference from Example 1 is that no reactive compatibilizer is added in step S2, and the screw speed is reduced to 180 rpm.
[0136] Comparative Example 3: The difference from Example 1 is that no polyether-modified polyester is added in step S3, and the hydrophilic layer material formulation is 97 parts by weight of copolyester and 3 parts by weight of mixed particles of nano silica and nano titanium dioxide.
[0137] Comparative Example 4: The difference from Example 1 is that in step S4, the melting temperature of each layer is adjusted so that the apparent viscosity ratio of the three melts at the spinning shear rate is η1:η2:η3=1:1.45:0.55.
[0138] Comparative Example 5: The difference from Example 1 is that the mass ratio of the three layers in step S4 is adjusted to 55:25:20.
[0139] Comparative Example 6: The difference from Example 1 is that the mass ratio of the three layers in step S4 is adjusted to 70:5:25.
[0140] Comparative Example 7: The difference from Example 1 is that polyether ester elastomer and multifunctional epoxy chain extender are not added in step S1, and the core layer material formulation is 96.5 parts by weight of polyester and 3.5 parts by weight of silanized silicon carbide whiskers.
[0141] Comparative Example 8: The difference from Example 1 is that no polyether ester elastomer is added in step S2, and the barrier layer material formulation is 90 parts by weight of copolyester, 9 parts by weight of liquid crystal copolyester, and 0.6 parts by weight of reactive compatibilizer.
[0142] Performance testing: To verify the improvement of the composite yarn of this application over existing reinforced polyester easy-to-clean yarn in terms of interface stability, radial barrier properties, hot water washing retention and surface release properties, the composite yarns obtained in Examples 1 to 8 and Comparative Examples 1 to 8 were subjected to structural characterization, hot water washing cycle, oily dirt migration, easy-to-clean grade and mechanical retention rate tests.
[0143] Before testing, the composite yarns obtained from each example and comparative example were equilibrated for 24 hours in a standard atmospheric environment with a temperature of 20℃±2℃ and a relative humidity of 65%±4%. For samples used to test fiber cross-sectional morphology, interfacial porosity, and dispersed phase size, composite yarns were directly used. For samples used to test stain-resistant properties, wetting properties, and multiple wash retention properties, single-sided knitted fabrics with a unit area mass of 160g / m² to 180g / m² were woven using a circular knitting machine with the same needle pitch. After weaving, the fabrics were pre-washed with deionized water, dried at 60℃, and equilibrated to ensure that the fabric structure, weight, and finishing state of each sample were consistent.
[0144] (1) Thermal response radial expansion and hot water interface adhesion test: A cross-sectional sample of the composite yarn was placed in a microscopic observation system with a temperature-controlled stage and kept at 25℃, 40℃, 50℃ and 60℃ for 5 minutes respectively. The change in the outer diameter of the barrier layer was measured. The radial expansion rate was calculated according to the formula R=(D50-D25) / D25×100%, where D25 is the outer diameter of the barrier layer at 25℃ and D50 is the outer diameter of the barrier layer at 50℃. The sample was treated in 50℃ hot water for 30 minutes and cooled to 25℃. The presence of annular debonding, local openings or interface cracks between the core layer and the barrier layer was observed by scanning electron microscopy. The average interface gap width of 30 cross sections was counted. This reflects the ability of the barrier layer to maintain adhesion with the core layer in the washing temperature zone, which corresponds to the technical effect of this application in inhibiting interlayer debonding and blocking dirt migration along the interface.
[0145] (2) Interfacial microporosity test after hot water washing: Fabric samples were subjected to 30 washing cycles according to the household washing procedure specified in GB / T 8629-2017 "Testing Procedures for Textiles - Household Washing and Drying". Samples were taken after every 10 washes. The washing temperature was 50℃, and the detergent dosage was 2g / L. After washing, the samples were rinsed with deionized water and dried at 60℃. After washing, the yarns were removed from the fabric, resin-embedded, and the cross-sections were polished. The yarns were then observed using a scanning electron microscope. Thirty cross-sections were randomly selected from each sample. Image analysis software was used to identify the micro-void regions around the reinforcing phase and at the interface between the core layer and the barrier layer. The proportion of the micro-void area to the cross-sectional area was calculated to reflect the degree of change in the micro-voids at the fiber interface after multiple washes, corresponding to the technical effect of reducing the probability of interface defect formation in this application.
[0146] (3) Radial migration depth test of oily dirt: Simulated oily dirt was prepared by mixing mineral oil, carbon black, and fluorescent dye at a mass ratio of 98.5:1.0:0.5. The simulated oily dirt was uniformly dripped onto the surface of the fabric sample and a pressure of 1 kPa was applied for 10 min. The sample was then placed in a 50°C washing solution and washed with shaking for 30 min. After rinsing and drying, the yarn was removed. The distribution of fluorescence signal in the fiber cross-section was observed using a laser confocal microscope. Starting from the outer surface of the hydrophilic layer, the maximum continuous migration distance of the fluorescence signal towards the fiber center was measured. 30 filaments were tested for each sample, and the average value was taken. The smaller the radial migration depth of the oily dirt, the better the radial barrier effect of the barrier layer, which directly corresponds to the technical effect of this application in improving the radial migration resistance of oily dirt from the hydrophilic layer to the core layer.
[0147] (4) Oil stain removability test: Referring to GB / T 28895-2012 "Protective Clothing - Oil-Resistant, Easily Stain-Removable, and Antistatic Protective Clothing", standard corn oil was dropped onto the fabric surface. After pressing the stain under specified pressure, the fabric was washed, rinsed, and dried according to household washing conditions. The washed samples were then compared with a standard rating card to assess the oil stain release level. The levels range from 1 to 5, with higher levels indicating easier removal of oil stains. Assessments were conducted after 1, 5, 10, 20, and 30 washes, recording the change in the stain-removability level with the number of washes. This reflects the ability of the yarn surface to retain its oil stain release properties after multiple washes.
[0148] (5) Tensile properties and retention rate of filaments after washing: The tensile strength of the composite yarn was tested according to GB / T 14344-2022 "Test Method for Tensile Properties of Chemical Fiber Filaments". Each sample was tested 20 times and the average value was taken. The initial sample and the sample after 30 hot water washing cycles were tested separately, and the tensile strength retention rate after washing was calculated. The higher the retention rate, the lower the degree of damage to the internal interface of the composite yarn after multiple washings and the better the structural integrity, which corresponds to the technical effect of maintaining stable performance after multiple hot water washings and tensile use in this application.
[0149] Testing equipment: A field emission scanning electron microscope, model SU8010, purchased from Hitachi High Technology Co., Ltd., was used for observing the cross-sectional morphology of fibers in the interfacial microporosity test after hot water washing and for measuring the interfacial gap in the thermal response fit test.
[0150] Transmission electron microscope, model Talos F200X, purchased from Thermo Fisher Scientific; used to assist in confirming the microstructure of the micropores at the interface around the reinforcing phase after hot water washing.
[0151] The laser confocal microscope, model LSM 900, purchased from Zeiss, was used for observing the distribution of fluorescence signals across fiber cross sections and measuring migration distance in the radial migration depth test of oily dirt.
[0152] The temperature-controlled heating stage, model THMS600, was purchased from Linkam and is used for in-situ measurement of fiber cross-sectional dimensions under different temperature conditions in thermal response radial expansion testing.
[0153] The electronic single-fiber strength tester, model YG001A, was purchased from Wenzhou Darong Textile Instrument Co., Ltd.; it is used to test the tensile properties and retention rate of filaments after washing.
[0154] The standard washing test chamber, model SW-12A, was purchased from Wenzhou Jigao Testing Instruments Co., Ltd.; it is used for conducting multiple washing cycle tests.
[0155] The standard light source box, model P60(6), was purchased from GTI Corporation, USA; it was used for the comparison and evaluation of the washed samples and the standard rating card in the test of the stain resistance of oily stains.
[0156] Table 1. Test Data for Examples and Comparative Examples
[0157] Data Analysis: The radial expansion rates of Examples 1 to 8 at 50°C ranged from 6.5% to 10.3%, and the interface gap width between the core layer and the barrier layer after treatment at 60°C did not exceed 0.09 μm, indicating that the barrier layer underwent reversible radial expansion within the washing temperature range and remained in contact with the core layer.
[0158] In Comparative Example 8, no polyether ester elastomer was added to the barrier layer material, and the radial expansion rate was only 0.5%, with an interfacial gap width of 1.25 μm. This indicates that polyether ester elastomer is a necessary component to impart thermal responsive expansion capability to the barrier layer. In Comparative Example 7, no polyether ester elastomer or multifunctional epoxy chain extender was added to the core layer material, and no viscoelastic film was added to the surface of the reinforcing phase. The interfacial gap width was 0.45 μm, which was significantly larger than that of the other examples. This indicates that the viscoelastic film and the barrier layer work together to inhibit interlayer debonding.
[0159] Regarding the interfacial microporosity after 30 washes, the microporosity of Examples 1 to 8 ranged from 1.6% to 2.5%, while the silicon carbide whisker of Comparative Example 1, which was not subjected to silanization pretreatment, had a microporosity as high as 8.5%; the microporosity of Comparative Example 7 was 6.2%. This demonstrates that silanization pretreatment and viscoelastic film are key means to reduce the probability of microporosity formation at the interface inside the core layer.
[0160] In Example 5, the reinforcing phase was a composite of silicon carbide whiskers and chopped aramid microfibers, with a total addition of 5.0 parts by weight. The microporosity was 1.6%, lower than 1.8% in Example 1 and 2.3% in Example 7, and also lower than 2.5% in Example 8. This indicates that as the reinforcing phase content increased from 1.5 parts by weight to 5.0 parts by weight, the microporosity gradually decreased. When the content was further increased to 6.0 parts by weight, the microporosity actually increased to 2.5%. This shows that appropriately increasing the reinforcing phase content is beneficial for bearing stress, but when the content is too high, the probability of uneven local viscoelastic film thickness increases, and it is difficult for some reinforcing phase surfaces to obtain complete viscoelastic film coverage, resulting in a rebound in the number of interfacial micropores.
[0161] The radial migration depth of oily dirt in Examples 1 to 8 ranged from 6.8 μm to 11.3 μm, which was generally lower than that of the comparative examples. The barrier layer mass ratio of Comparative Example 6 was only 5%, and the annular structure was interrupted in more than 15% of the cross-section, with a migration depth of 19.3 μm. The migration depth of Comparative Example 8 was 22.4 μm, which was the highest value among all samples, indicating that the continuity of the barrier layer and the thermal response adhesion both play an important role in blocking the radial migration of oily dirt.
[0162] The migration depth of Example 5 was 6.8 μm, which was lower than that of Example 6 (10.5 μm) and Example 7 (7.2 μm). In Example 5, the amount of liquid crystal copolyester added to the barrier layer was 11 parts by weight and the amount of polyether ester elastomer was 28 parts by weight. In Example 7, the amount of liquid crystal copolyester was as high as 15 parts by weight, but the amount of polyether ester elastomer was only 12 parts by weight, and the migration depth increased to 7.2 μm. This shows that the barrier effect does not increase linearly with the content of liquid crystal copolyester. When the content of polyether ester elastomer is insufficient, the radial expansion and adhesion ability of the barrier layer in the washing temperature zone are limited. Although there are many orientation barrier paths formed by the liquid crystal copolyester dispersed phase, small gaps appear due to insufficient interlayer adhesion, and oil stains can still penetrate along the interface, so the migration depth increases instead of decreasing.
[0163] Regarding the stain-removability rating after 30 washes, the ratings of Examples 1 to 8 ranged from 3.8 to 4.4. In Comparative Example 3, no polyether-modified polyester was added to the hydrophilic layer, and the stain-removability rating plummeted to 1.5. This confirms that the hydrophilic segments of the polyether-modified polyester are the material basis for achieving the surface release function.
[0164] The grade of Example 5 is 4.4, Example 8 is 4.3, and Example 7 is 3.8. In Example 5, the content of polyether-modified polyester is 34 parts by weight and the content of nano-inorganic particles is 4 parts by weight; in Example 8, the content of polyether-modified polyester is 30 parts by weight and the content of nano-inorganic particles is 5 parts by weight; in Example 7, the content of polyether-modified polyester is 20 parts by weight and the content of nano-inorganic particles is 1.5 parts by weight. This shows that appropriately increasing the content of polyether-modified polyester and nano-inorganic particles can improve the easy-to-clean grade. However, when the content of nano-inorganic particles increases to 5 parts by weight, the grade does not improve further, showing extreme value characteristics. This indicates that when the content of nano-inorganic particles is too high, the risk of local agglomeration increases, the uniformity of the surface hydrophilic groove structure decreases, and the easy-to-clean grade tends to level off or even decline.
[0165] Regarding the retention rate of tensile strength after 30 washes, the retention rates of Examples 1 to 8 ranged from 83.5% to 89.6%, while those of Comparative Examples 1 and 7 decreased to 72.3% and 74.6%, respectively. This indicates that the interfacial micropores gradually expanded during repeated washing and stretching, leading to a decline in mechanical properties. The retention rate of Example 5 was 89.6%, and that of Example 8 was 83.5%, showing an extreme inflection point of first increasing and then decreasing.
[0166] When the content of the reinforcing phase is 5.0 parts by weight, the viscoelastic film is intact and uniformly dispersed, and the degree of interface damage accumulation is the lowest after multiple washes. When the content increases to 6.0 parts by weight, as mentioned above, the microporosity increases, the interface damage spreads faster during washing, and the retention rate decreases.
[0167] It should be noted that the order of description of the embodiments in this application is not intended to limit the priority of the embodiments.
[0168] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used in this application and in its specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0169] The embodiments of this application have been described above with reference to the accompanying drawings. However, this application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many forms under the guidance of this application without departing from the spirit and scope of protection of the claims. All equivalent transformations made under the inventive concept of this application using the content of this application's specification and drawings, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this application.
Claims
1. A composite yarn, characterized in that, include: Core layer; A barrier layer, sleeved outside the core layer, includes a first matrix and a water-blocking phase dispersed in the first matrix. The water-blocking phase includes a hydrophobic polymer, and the water-blocking phase is arranged in multiple layers at intervals in the radial direction of the composite yarn. A hydrophilic layer, disposed outside the barrier layer, includes a second matrix and modified particles dispersed in the second matrix, wherein the modified particles have hydrophilic segments.
2. The composite yarn according to claim 1, characterized in that, Each of the water-blocking phases extends along the axial direction of the composite yarn.
3. The composite yarn according to claim 1, characterized in that, The coefficient of thermal expansion of the barrier layer is less than that of the core layer.
4. The composite yarn according to claim 2 or 3, characterized in that, The barrier layer comprises, by weight, 55 to 80 parts of copolyester, 12 to 32 parts of polyether ester elastomer, 3 to 15 parts of liquid crystal copolyester, and 0.2 to 1.0 parts of reactive compatibilizer; And / or, the water-blocking phase has a radial dimension of 50 nm to 500 nm in the composite yarn; And / or, the water-blocking phase is an oriented dispersed phase formed from a liquid crystal copolyester.
5. The composite yarn according to claim 1, characterized in that, The modified particles comprise nano-inorganic particles, and the hydrophilic segments are attached to the surface of the nano-inorganic particles.
6. The composite yarn according to claim 5, characterized in that, The hydrophilic layer comprises, by weight, 55 to 82 parts copolyester, 15 to 40 parts polyether-modified polyester, and 0.5 to 5.0 parts nano-inorganic particles; And / or, the nano-inorganic particles are nano-silica and / or nano-titanium dioxide; And / or, the average particle size of the nano-inorganic particles is 20 nm to 100 nm.
7. The composite yarn according to claim 1, characterized in that, The surface of the hydrophilic layer has hydrophilic grooves extending along the fiber axis.
8. The composite yarn according to claim 7, characterized in that, The depth of the hydrophilic groove is 0.2 μm to 1.5 μm, and the width is 0.5 μm to 5 μm.
9. The composite yarn according to claim 1, characterized in that, The core layer includes a third matrix and a reinforcing phase dispersed in the third matrix. The third matrix includes polyester, and the surface of the reinforcing phase is coated with a viscoelastic film, which includes a polyester-compatible material.
10. The composite yarn according to claim 9, characterized in that, The thickness of the viscoelastic film is 20 nm to 150 nm; And / or, the viscoelastic film has a dynamic mechanical loss factor tanδ peak value in the temperature range of 35°C to 60°C; And / or, the core layer comprises, by weight, 85 to 96 parts polyester, 2 to 10 parts polyether ester elastomer, 1.5 to 6.0 parts reinforcing phase and 0.05 to 0.8 parts multifunctional epoxy chain extender; And / or, the reinforcing phase is one or more of silicon carbide whiskers, alumina whiskers, chopped basalt microfibers, or chopped aramid microfibers.
11. A method for preparing a composite yarn, characterized in that, Includes the following steps: Preparation of core layer material; A first substrate and a hydrophobic polymer are melt-blended to disperse the hydrophobic polymer in the first substrate, thereby obtaining a barrier layer material. The second substrate and the modified particles are melt-blended to obtain a hydrophilic layer material, wherein the modified particles have hydrophilic segments; The barrier layer and the hydrophilic layer are sequentially wrapped around the core layer material and then coaxially spun and drawn to obtain the composite yarn.
12. The preparation method according to claim 11, characterized in that, The preparation of the core layer material includes: silanizing the reinforcing phase as a pretreatment; melt-blending the pretreated reinforcing phase with polyester, polyether ester elastomer and multifunctional epoxy chain extender to form a viscoelastic film in situ on the surface of the reinforcing phase, thereby obtaining the core layer material. And / or, the first substrate comprises a copolyester and a polyether ester elastomer, and the hydrophobic polymer comprises a liquid crystal copolyester; And / or, the mass ratio of the core layer material, barrier layer material and hydrophilic layer material is 60-78:8-20:12-30; And / or, the apparent viscosities of the core layer material, the barrier layer material, and the hydrophilic layer material during the spinning process are η1, η2, and η3, respectively, with η1:η2:η3 = 1:0.80-1.20:0.60-1.00; And / or, the total draw ratio of the pull is 2.8 to 4.0 times.